2006
DOI: 10.1038/nn1675
|View full text |Cite
|
Sign up to set email alerts
|

Negative functional MRI response correlates with decreases in neuronal activity in monkey visual area V1

Abstract: Most functional brain imaging studies use task-induced hemodynamic responses to infer underlying changes in neuronal activity. In addition to increases in cerebral blood flow and blood oxygenation level-dependent (BOLD) signals, sustained negative responses are pervasive in functional imaging. The origin of negative responses and their relationship to neural activity remain poorly understood. Through simultaneous functional magnetic resonance imaging and electrophysiological recording, we demonstrate a negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

103
725
10
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 824 publications
(854 citation statements)
references
References 49 publications
103
725
10
3
Order By: Relevance
“…A relative increase in theta oscillations could therefore lead to a decrease in the BOLD signal. Simultaneous recording of hemodynamic responses and intracortical electrophysiological responses in the visual cortex of cat (Niessing et al, 2005) and monkey (Logothetis et al, 2001;Shmuel et al, 2006) corroborate this notion. In the cat, Niessing et al (2005) reported negative correlations in between lower frequencies (delta and theta) and the hemodynamic responses, and strong positive correlations with gamma band activity during visual stimulation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A relative increase in theta oscillations could therefore lead to a decrease in the BOLD signal. Simultaneous recording of hemodynamic responses and intracortical electrophysiological responses in the visual cortex of cat (Niessing et al, 2005) and monkey (Logothetis et al, 2001;Shmuel et al, 2006) corroborate this notion. In the cat, Niessing et al (2005) reported negative correlations in between lower frequencies (delta and theta) and the hemodynamic responses, and strong positive correlations with gamma band activity during visual stimulation.…”
Section: Discussionsupporting
confidence: 55%
“…In the cat, Niessing et al (2005) reported negative correlations in between lower frequencies (delta and theta) and the hemodynamic responses, and strong positive correlations with gamma band activity during visual stimulation. Shmuel et al (2006) found that the negative BOLD response in the monkey primary visual cortex during partial visual field stimulation is accompanied with decreased neural activity in the gamma range (30-130 Hz). Logothetis et al (2001) showed that increased gamma band activity during visual stimulation is tightly coupled to the positive BOLD response.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have provided evidence of a neural component to the inhibitory rebound. Shmuel et al (2006Shmuel et al ( , 2002 have studied the origin of the negative BOLD activation in cortical regions adjacent to those receiving direct projections from stimulated retina and shown that it cannot be attributed to blood dynamics but must be a result of a reduction in the neuronal signal in those regions. Such studies imply that it is reasonable to attribute negative BOLD signals to inhibitory suppression of neural activity, especially in the present situation when (1) there is no diVerence in the local stimulation between the test-and the null-epochs, (2) and the only sites of activation are remote from the zone of reduced BOLD response.…”
Section: Analysis: a Recurrent Wgure/ground Modelmentioning
confidence: 99%
“…a is a positive number representing the intensity of the stimulus. It has been reported in [29,15] that the percent of change in neuronal signal is in the 25% − 50% ranges for excitatory activity during visual stimulation conditions, i.e., a ∈ [0.25, 0.5].…”
Section: Nomenclature and Assumptionsmentioning
confidence: 99%